Access and use of oxytocin for postpartum haemorrhage prevention: a pre-post study targeting the poorest in six Mesoamerican countries - Ali H Mokdad; Aruna M Kamath; Alexandra M Schaefer; Erin B Palmisano; Casey K Johanns; Alvaro Gonzalez Marmol; Mauricio Dinarte Mendoza; Karla Schwarzbauer; Paola Zúñiga-Brenes; Diego Ríos-Zertuche; Emma Iriarte; Bernardo Hernandez Prado (BMJ Open)
Objectives Haemorrhage remains the leading cause of maternal mortality in Central America. The Salud Mesoamérica Initiative aims to reduce such mortality via performance indicators. Our objective was to assess the availability and administration of oxytocin, before and after applying Salud Mesoamérica Initiative interventions in the poorest health facilities across Central America.Design Pre-post study.Setting 166 basic-level and comprehensive-level health facilities in Belize, Guatemala, Honduras, Mexico, Nicaragua and Panama.Participants A random sample of medical records for uncomplicated full-term deliveries (n=2470) per International Classification of Diseases coding at baseline (July 2011 to August 2013) and at first-phase follow-up (January 2014 to October 2014).Interventions A year of intervention implementation prior to first-phase follow-up data collection focused on improving access to oxytocin by strengthening supply chains, procurement, storage practices and pharmacy inventory monitoring, using a results-based financing model.Primary and secondary outcome measures Oxytocin availability (primary outcome) and administration (secondary outcome) for postpartum haemorrhage prevention.Results Availability of oxytocin increased from 82.9% to 97.6%. Oxytocin administration increased from 83.6% to 88.4%. Significant improvements were seen for availability of oxytocin (adjusted OR (aOR)=8.41, 95% CI 1.50 to 47.30). Administration of oxytocin was found to be significantly higher in Honduras (aOR=2.96; 95% CI 1.00 to 8.76) in reference to Guatemala at follow-up.Conclusion After interventions to increase health facility supplies, the study showed a significant improvement in availability but not administration of oxytocin in poor communities within Mesoamerica. Efforts are needed to improve the use of oxytocin.